On the formation of spin dependent double layer structure in astrophysical plasmas. Issue 7 (10th May 2021) - Khanum, Uzma; Iqbal, Zafar; Shamir, Muhammad; Murtaza, Ghulam
Abstract: Double layers (DLs) are nonlinear structures, and are thought to be responsible for particle acceleration in laboratory plasmas and astrophysical plasmas. In this paper, the existence of spin dependent DLs structure is explored using separate spin evolution quantum hydrodynamic model. Based on reductive perturbation method, we derived an extended Korteweg–de Vries (eKdV) equation to demonstrate the existence and nature of DLs. We found that spin polarization significantly enhanced the amplitude of the electrostatic potential associated with DLs. Further, spin polarization also increases the depth and width of the Sagdeev potential. It is noted that the contribution of Bohm potential effect is essential for the formation of DLs structure. Our results may be helpful to explain the phenomenon of particle acceleration in dense astrophysical environments specifically in a white dwarf.